Free Air in the Cavernous Sinus Secondary to Acute Isolated Sphenoid Sinusitis - Matsuo, Satoshi (NMC Case Rep J, 2016)
Pneumocephalus is a rare but important complication of acute isolated sphenoid sinusitis (ISS). If not adequately treated, it may cause serious neurological and life-threatening complications. We report the presence of free air in the cavernous sinus arising from intracranial extension of acute ISS. A 41-year-old healthy man presented to our department with a 7-day history of headache. Neurological examination revealed no meningitis, and cerebrospinal fluid culture was negative. A head computed tomography (CT) and magnetic resonance imaging on admission revealed sinusitis in the sphenoid sinus and presence of air in the cavernous sinus. We started an antibiotic treatment and the patient’s fever immediately decreased and the inflammatory response improved. In addition, the bilateral retro-orbital headache diminished. A repeated head CT scan revealed that fluid retention in the sphenoid sinus and air in the cavernous sinus had disappeared. To our knowledge, this is the fifth case of pneumocephalus accompanied by acute ISS reported in the literature and the first case report of intracranial air located only in the cavernous sinus. Meningitis accompanied by pneumocephalus can be a warning sign for poor outcome in patients with ISS.